A MODEL OF LEADERSHIP ACCORDING TO GARÃVÃSADHAMMA IV OF PRIMARY SCHOOL ADMINISTRATORS UNDER BANGKOK METROPOLITAN ADMINISTRATION - Adhipañño (Anuhanayon), Phrakrupalad Natthawat; Srivichai, Suddhipong; Dhanapañño, Phramaha Sombat (Journal of Educational Review Faculty of Education in MCU, 2020)
This research paper aimed to propose a model of leadership according to Garãvãsadhamma IV of primary school administrators under Bangkok Metropolitan Administration. Mixed methods research was conducted and three research steps were designed. Step 1: Study leadership of primary school administrators using a questionnaire to collect from a sample group of 390 primary school administrators and teachers. Data were analyzed by descriptive statistics such as percentage, frequency, mean, standard deviation. Step 2: study the leadership style of administrators according to Garãvãsadhamma IV by interviewing 24 key informants, the data was analyzed by content analysis according to the interview form. Step 3: proposing the model of leadership according to Garãvãsadhamma IV of primary school administrators under Bangkok Metropolitan Administration by conducting focus group discussion of 9 experts, the data was analyzed by content analysis based on the guideline questions for focus group discussion. The results of the research showed that a model of leadership according to Garãvãsadhamma IV of primary school administrators under Bangkok Metropolitan Administration consisted of 4 compositions: (1) Principles, (2) Goals, (3) Operational systems, and (4) Operational processes. Three areas of leadership principles of school administrators were applied which consisted of (1) the visionary, (2) Vithuro with knowledge and ability, (3) Nissayasampanno, have human relations to integrate Garãvãsadhamma IV, namely (1) truth, (2) control of emotions, (3) tolerance, and (4) sacrifice.